The dynamics of music psychotherapy - Bruscia, Kenneth E. (Barcelona Publishers, 1998)
A long-overdue exploration of transference and countertransference in the field, this book presents the work of leading pioneers in psychodynamically oriented music therapy. After an introduction to the dynamics and methodology of music psychotherapy, the book provides in-depth analyses of transference and countertransference as they are manifested in various approaches to using improvisation, songs, and music imagery. The chapters are both theoretical and clinical including perspectives of both therapist and client. Aside from being a first in music therapy, this book extends the horizons of
Keywords: Music therapy; Psychotherapy